Control of Clostridium difficile infection in the hospital setting. Issue 4 (April 2014) - Wiuff, Camilla; Murdoch, Heather; Coia, John E
<x xml:space="preserve">Abstract</x> Clostridium difficile infection (CDI) has emerged as a leading challenge in the control of healthcare-associated infection (HCAI). The epidemiology of CDI has changed dramatically, this is associated with emergence of 'hypervirulent' strains, particularly PCR ribotype 027. Despite the epidemic spread of these strains, there are recent reports of decreasing incidence from healthcare facilities where multi-facetted targeted control programs have been implemented. We consider these changes in epidemiology and reflect on the tools available to control CDI in the hospital setting. The precise repertoire of measures adopted and emphasis on different interventions will vary, not only between healthcare systems, but also within different institutions within the same healthcare system. Finally, we consider both the sustainability of reductions already achieved, and the potential to reduce CDI further. This takes account of newly emerging data on more recent changes in the epidemiology of CDI, and the potential of novel interventions to decrease the burden of disease.